Effect of Core Geometry on Frequency Correlations and Channel Capacity of a Multimode Optical Fiber - Henry C. Hammer; Ravitej Uppu (Advanced Photonics Research)
Photons are the fundamental carriers of classical and quantum information across long distances via optical fibers. Multimode fibers with many transverse optical modes can support high‐capacity communication through space‐division multiplexing. While spatial correlations in light transmission via fibers have been investigated for counteracting mode mixing, less is known about frequency correlations, which are critical for high‐capacity communication using ultrashort pulses. This study uses complex wavefront shaping methods to investigate how core geometry affects the frequency correlation bandwidth of structured wavefronts in circular and rectilinear‐core fibers. Measurements reveal that rectilinear‐core fibers exhibit up to a 40% increase in frequency correlation bandwidth compared to circular core fibers, particularly when focusing light away from the fiber center—common in spatially multiplexed optical communication. This enhanced bandwidth results in a 20% boost in optical communication channel capacity, highlighting the potential of rectilinear core fibers. Furthermore, this observation of novel spatiotemporal wave correlations could be exploited for application of rectilinear core fibers in chip‐to‐chip interconnects for photonic quantum processors, contributing to scale up of photonic quantum technologies.